Extracellular ATP plays an important role in systemic wound response activation - Myers, Ronald J; Fichman, Yosef; Stacey, Gary; Mittler, Ron (Plant physiology (Bethesda), 2022)
Mechanical wounding occurs in plants during biotic or abiotic stresses and is associated with the activation of long-distance signaling pathways that trigger wound responses in systemic tissues. Among the different systemic signals activated by wounding are electric signals, calcium, hydraulic, and reactive oxygen species (ROS) waves. The release of glutamate (Glu) from cells at the wounded tissues was recently proposed to trigger systemic signal transduction pathways via GLU-LIKE RECEPTORs (GLRs). However, the role of another important compound released from cells during wounding (extracellular ATP [eATP]) in triggering systemic responses is not clear. Here, we show in Arabidopsis (Arabidopsis thaliana) that wounding results in the accumulation of nanomolar levels of eATP and that these levels are sufficient to trigger the systemic ROS wave. We further show that the triggering of the ROS wave by eATP during wounding requires the PURINORECEPTOR 2 KINASE (P2K) receptor. Application of eATP to unwounded leaves triggered the ROS wave, and the activation of the ROS wave by wounding or eATP application was suppressed in mutants deficient in P2Ks (e.g. p2k1-3, p2k2, and p2k1-3p2k2). In addition, expression of systemic wound response (SWR) transcripts was suppressed in mutants deficient in P2Ks during wounding. Interestingly, the effect of Glu and eATP application on ROS wave activation was not additive, suggesting that these two compounds function in the same pathway to trigger the ROS wave. Our findings reveal that in addition to sensing Glu via GLRs, eATP sensed by P2Ks plays a key role in the triggering of SWRs in plants.